Peran Keuangan Syariah Dalam Mendorong Pertumbuhan Ekonomi Dan Inklusi Keuangan Di Indonesia - Sobarna, Nanang; Salsabila, Alya; Sholihatunnisa, Sholihatunnisa (Program Studi Ekonomi Syariah Institut Manajemen Koperasi Indonesia, 2025)
The Islamic financial system is crucial for driving economic growth in developing countries like Indonesia. Through its functions as a fund intermediary, liquidity provider, investment financing, and risk management, the financial system plays a strategic role in driving a country's economic growth. Based on the principles of justice and the prohibition of usury, the Islamic financial system has the potential to drive economic growth and financial inclusion in Indonesia. The purpose of this study is to uncover the role of the Islamic financial system in promoting inclusive economic development in Indonesia. This study employed a qualitative methodology involving the use of descriptive analytical techniques. Data were collected through literature research from accredited national journals, indexed international journals, and other relevant sources. Research shows that Islamic financial assets in Indonesia will increase by 12.48% annually, reaching IDR 2,756.45 trillion by June 2024. The current market share of Islamic finance is 11.41%. This demonstrates public interest in Islamic financial products. Furthermore, as of June 2024, the collection of zakat, infaq, sadaqah, and other social funds reached IDR 26.1 trillion, indicating significant growth in Islamic social funds. To maximize the role of Islamic finance in driving Indonesia's economic growth, all stakeholders must work together to improve financial literacy and inclusion, and strengthen regulations, so that the goal of building an inclusive and equitable economy can be achieved. Keywords: Islamic Financial System, Economic Growth, Financial Inclusion